Location, investment and regional policy: the contribution of the average effective tax rate theory - Michel Mignolet; Nathalie Eyckmans; Olivier Meunier (European Regional Science Association (ERSA), 2004)
For decades, most industrialised countries have implemented some forms of fiscal and financial incentives to stimulate fixed capital formation. Tax cuts and capital grants are of great use in regional policy. Since these instruments mobilise huge amounts of public resources the issue of their efficiency is of particular interest for policymakers. The impact of taxation on investment income was traditionally apprehended through models measuring the effective tax rate on marginal investments. However recent literature, especially Devereux and Griffith (2002), showed the interest of resorting to an alternative tax measure – the effective average tax rate (EATR) - when firms face discrete investment choices that are expected to generate positive economic rent before tax. This effective average tax rate is defined by the difference between the net present value of the rent of the investment before and after taxes scaled by the net present value of the pre-tax income stream. In this sense, the effective average tax rate developed by Devereux and Griffith (2002) seems to be particularly relevant to shed a new light on the relative effectiveness of tax cuts and capital subsidy grants. In this paper we intend to compare the costs for public authorities to lower the corporate tax rate or to grant a capital subsidy. These public costs are directly affected by the variation of the after-tax revenue earned by the shareholder. The extent to which each policy must be implemented depends on the channel chosen by the government to stimulate investment. We pay attention to two of these channels: a reduction of the capital cost and a lowering of the EATR. Finally, in order to illustrate the relevance of our approach, we developed a numerical example for the Belgian case. JEL Classification: H25, H32 and R58
Keywords: H25; H32; R58; 330